Higher levels of secretory IgA are associated with low disease activity index in patients with reactive arthritis and undifferentiated spondyloarthritis (2017)
Introduction: Both reactive arthritis (ReA) and undifferentiated spondyloarthritis (uSpA) belong to the group of autoinflammatory diseases called spondyloarthritis (SpA). Hypotheses have been proposed about a relationship between the intestinal mucosa and inflammation of joint tissues. The role of immunoglobulin IgA or secretory immunoglobulin A (SIgA) in the inflammatory and/or clinical activity of patients with SpA remains poorly understood. Objective: To evaluate the status of total IgA and SIgA, and the association among the levels of SIgA, IgA, IgA anti-Chlamydia trachomatis, and anti-Shigella spp. with the disease activity measures, erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) levels, was compared in a cohort of patients with ReA and uSpA and healthy subjects. Methods: This was a cross-sectional study. The serum concentrations of SIgA, IgA anti-C. trachomatis, anti-Shigella spp., and total IgA were measured. Disease activity was measured in each patient by means of Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) and Ankylosing Spondylitis Disease Activity Score (ASDAS). Statistical analysis did include as bivariate evaluation, comparisons by Student’s t-test, Kruskal–Wallis test, and U Mann–Whitney test, with a multivariate evaluation by principal components analysis (PCA). A correlation analysis was carried out using the Pearson correlation coefficient and a linear regression models. All analysis were made using Stata version 11.2® for Windows, R V3.3.21. Statistical significance was defined a p-value <0.05. Results: In all, 46 patients (78.2% men; mean age, 34.8 ± 12.3 years) and 53 controls (41% men; mean age, 32 ± 11.4 years) were included in the study. The mean serum levels of SIgA were higher in SpA patients than in healthy subjects (p < 0.001). Only SIgA levels correlated with disease activity: BASDAI (r = −0.42, p = 0.0046), ASDAS-CRP (r = −0.37, p = 0.014), and ASDAS-ESR (r = −0.45, p = 0.0021). The negative correlation between SIgA and all activity indices was higher in HLA-B27-positive patients (BASDAI r = −0.70, p = 0.0009, ASDAS-CRP r = −0.58, p = 0.0093, and ASDAS-ESR r = −0.57, p = 0.0083). The PCA showed three factors: the first component was constituted by variables referred as clinical activity measures, the second did include the serological activity markers, and the last component was compounded by age and symptoms time. Conclusion: Elevated serum levels of SIgA were found to be related with low disease activity in patients with ReA and uSpA.